Roles of Non-Coding RNAs in Primary Biliary Cholangitis - Zhang, Yaqin; Jiao, Ziying; Chen, Mingwei; Shen, Bing; Shuai, Zongwen (Frontiers in Molecular Biosciences, 2022)
Primary biliary cholangitis (PBC) is an autoimmune-mediated chronic cholestatic liver disease, fatigue, and skin itching are the most common clinical symptoms. Its main pathological feature is the progressive damage and destruction of bile duct epithelial cells. Non-coding RNA (NcRNA, mainly including microRNA, long non-coding RNA and circular RNA) plays a role in the pathological and biological processes of various diseases, especially autoimmune diseases. Many validated ncRNAs are expected to be biomarkers for the diagnosis or treatment of PBC. This review will elucidate the pathogenesis of PBC and help to identify potential ncRNA biomarkers for PBC.